System Center 2012 Configuration Manager Unleashed - Meyler, Kerrie (Sams, 2012)
This is the comprehensive reference and technical guide to Microsoft System Center Configuration Manager 2012. A team of expert authors offers step-by-step coverage of related topics in every feature area, organized to help IT professionals rapidly optimize Configuration Manager 2012 for their requirements, and then deploy and use it successfully. The authors begin by introducing Configuration Manager 2012 and its goals, and explaining how it fits into the broader System Center product suite. Next, they fully address planning, design, and implementation. Finally, they systematically cover each of Configuration Manager 2012's most important feature sets, addressing issues ranging from configuration management to software distribution. Readers will learn how to use Configuration Manager 2012's user-centric capabilities to provide anytime/anywhere services and software, and to strengthen both control and compliance. The first book on Configuration Manager 2012, System Center Configuration Manager 2012 Unleashed joins Sams' market-leading series of books on Microsoft's System Center product suite: books that have achieved go-to status amongst IT implementers and administrators worldwide.
Online resource; Title from title page (viewed July 18, 2012)